2014
DOI: 10.1016/j.molcel.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Destabilizing LSD1 by Jade-2 Promotes Neurogenesis: An Antibraking System in Neural Development

Abstract: Histone H3K4 demethylase LSD1 plays an important role in stem cell biology, especially in the maintenance of the silencing of differentiation genes. However, how the function of LSD1 is regulated and the differentiation genes are derepressed are not understood. Here, we report that elimination of LSD1 promotes embryonic stem cell (ESC) differentiation toward neural lineage. We showed that the destabilization of LSD1 occurs posttranscriptionally via the ubiquitin-proteasome pathway by an E3 ubiquitin ligase, Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 45 publications
(50 reference statements)
0
90
0
Order By: Relevance
“…14). Notably, the protein product of JADE2 has been found to act as a ubiquitin-ligase to regulate the activity of the histone demethylase LSD1 in neuronal differentiation [76], suggesting that it may play a role in shifting the immune-related epigenetic landscape in TNBC samples. Interactive figures for these two differential correlation networks are available online (see “Availability and requirements”).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…14). Notably, the protein product of JADE2 has been found to act as a ubiquitin-ligase to regulate the activity of the histone demethylase LSD1 in neuronal differentiation [76], suggesting that it may play a role in shifting the immune-related epigenetic landscape in TNBC samples. Interactive figures for these two differential correlation networks are available online (see “Availability and requirements”).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In order to gain insight into the regulation of LSD1 function after AIE exposure, we measured mRNA transcripts of selected proteins known to interact with LSD1 in the amygdala of adult rats after AIE (Figure 5A). Jade-2 was recently reported to degrade the LSD1 protein and target it for proteasomal degradation (Han et al, 2014). However, our results show that Jade2 mRNA is unaltered in the amygdala after AIE in adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…A checkpoint based on normal follicle size at stage 6 is unlikely, since our experiments showed that the M-E transition can be accelerated and take place in undersized follicles. However, regulated changes in Lsd1 protein stability may play a role, since a specific ubiquitin ligase, Jade 2, targets Lsd1 for degradation via the proteasome pathway in mammalian neural progenitors (Han et al 2014), while Lsd1 turnover is attenuated by expression of the ubiquitin-specific protease Usp28 in breast cancer cells (Wu et al 2013). Perhaps the most interesting possibility is that gradual changes in the cellular chromatin state mediated by Lsd1/CoREST activity act as a ''differentiation clock.''…”
Section: Discussionmentioning
confidence: 99%